A rationally designed amino-borane complex in a metal organic framework: a novel reusable hydrogen storage and size-selective reduction material1. Issue 36 (4th May 2015) - Wang, Xinbo; Xie, Linhua; Huang, Kuo-Wei; Lai, Zhiping
<x xml:space="preserve">Abstract</x> A novel microporous material UiOAB was synthesized, which can act as both a reusable hydrogen chemical storage material and a size-selective reducing agent.